Against the Devil in History : Poems, Short Stories, Essays, Fragments - Wat, Aleksander (Book collections on Project MUSE., 2018)
"Collected poems, essays, short stories, and fragmentary writings by Polish poet Aleksander Wat in English translation, annotated and with an introduction"--